DAYA SERAP AIR DAN KANDUNGAN SERAT (FIBER CONTENT) KOMPOSIT POLIESTER TIDAK JENUH (UNSATURATED POLYESTER) BERPENGISI SERAT TANDAN KOSONG SAWIT DAN SELULOSA - Michael, Elmer Surya, Halimatuddahliana (Universitas Sumatera Utara, 2013)
This study was aimed to investigate the effect of empty fruit bunch palm oil and cellulose content as filler in water absorption and fibre volume fraction of the unsaturated polyester composites. The composites were made by hand-lay up method by mixing unsaturated polyester with the composition of each fillers (empty fruit bunch palm oil and cellulose) of 5,10,15,20 wt%. The parameter which was carried on the prepared samples was water absorption for each sample every 24 hours until the composites have constant absorption. It was found that the addition of fillers to the matrix caused the water absorption of composites increased at each of composition of fillers (empty fruit bunch palm oil and cellulose) and the fibre volume fraction increased as the filler content increase.